Dual Roles of IL-27 in Cancer Biology and Immunotherapy - Marina Fabbi; Grazia Carbotti; Silvano Ferrini (Mediators of Inflammation)
IL-27 is a pleiotropic two-chain cytokine, composed of EBI3 and IL-27p28 subunits, which is structurally related to both IL-12 and IL-6 cytokine families. IL-27 acts through a heterodimer receptor consisting of IL-27Rα (WSX1) and gp130 chains, which mediate signaling predominantly through STAT1 and STAT3. IL-27 was initially reported as an immune-enhancing cytokine that supports CD4+ T cell proliferation, T helper (Th)1 cell differentiation, and IFN-γ production, acting in concert with IL-12. However, subsequent studies demonstrated that IL-27 displays complex immune-regulatory functions, which may result in either proinflammatory or anti-inflammatory effects in relationship to the biological context and experimental models considered. Several pieces of evidence, obtained in preclinical tumor models, indicated that IL-27 has a potent antitumor activity, related not only to the induction of tumor-specific Th1 and cytotoxic T lymphocyte (CTL) responses but also to direct inhibitory effects on tumor cell proliferation, survival, invasiveness, and angiogenic potential. Nonetheless, given its immune-regulatory functions, the effects of IL-27 on cancer may be dual and protumor effects may also occur. Here, we will summarize IL-27 biological activities and its functional overlaps with the IFNs and discuss its dual role in tumors in the light of potential applications to cancer immunotherapy.